O leitor-sujeito : uma proposta teórico-metodológica de leitura pelo viés da teoria enunciativa de Benveniste - Aldrovandi, Makeli (2018)
We proposed, through this work, to elaborate a reading itinerary based on Benveniste's Enunciative Theory. To do so, we conceptualized enunciative reading as an act of response to the text, in which, by (re)creating the meanings of this text, the reader becomes readersubject, responsible for the new enunciation that the reading is. We aimed, first, to define the concept of enunciative reading and, then, to elaborate a theoretical methodological approach of enunciative reading that leads the reader to understand a text in its totality, by raising awareness of the strategies and linguistic resources that the author, as subject of the enunciation of their text, used to mark themselves in their statement. In order to do so, we elaborated questions about three texts of the genre opinion article, widely used in high school classrooms. These questions were based on three enunciative principles that we drew from the readings of Benveniste. They are: the principle of intersubjectivity, the principle of reference, and the principle of form and meaning as twin notions. Then, these same questions were discussed from the point of view of the principles in order to make their relationship with each of them explicit. Finally, we elaborated a table with a compilation of types of questions that can be created from our principles. The purpose of the table is to guide teachers who become interested in the approach. We believe it is relevant to carry out a research that aims to create a reading guide, since there is no knowledge of similar research in Linguistics. The differential of this work is precisely in not being a test of reading comprehension capacity, but rather a guide that proposes to take the reader along the paths of reading, in order to make him perceive himself as the subject responsible for his enunciation, i.e., by his reading, and not just a decoder of messages whether explicit or hidden in between the lines of the text.